2019
DOI: 10.1609/aaai.v33i01.33012379
|View full text |Cite
|
Sign up to set email alerts
|

Enriching Non-Parametric Bidirectional Search Algorithms

Abstract: NBS is a non-parametric bidirectional search algorithm proven to expand at most twice the number of node expansions required to verify the optimality of a solution. We introduce new variants of NBS that are aimed at finding all optimal solutions. We then introduce an algorithmic framework that includes NBS as a special case. Finally, we introduce DVCBS, a new algorithm in this framework that aims to further reduce the number of expansions. Unlike NBS, DVCBS does not have any worst-case bound guarantees, but in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…NBS (Chen et al 2017) and NBB (Alcázar, Barley, and Riddle 2019), both near-optimal algorithms. NBB is equivalent to NBS a (Shperberg et al 2019a) apart from its pseudocode; we choose NBB because its bucket-based implementation is the basis for DBS and DBBS (described below). • DVCBS and DVCBS a .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NBS (Chen et al 2017) and NBB (Alcázar, Barley, and Riddle 2019), both near-optimal algorithms. NBB is equivalent to NBS a (Shperberg et al 2019a) apart from its pseudocode; we choose NBB because its bucket-based implementation is the basis for DBS and DBBS (described below). • DVCBS and DVCBS a .…”
Section: Methodsmentioning
confidence: 99%
“…• DVCBS and DVCBS a . Developed by Shperberg et al (2019a), the reported state of the art. • GBFHS and GBFHS e .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many enhancements have been proposed for IDA * (Sarkar et al 1991;Wah and Shang 1994;Burns and Ruml 2013;Stern et al 2010;Bu et al 2014;Sharon, Felner, and Sturtevant 2014;Hatem, Burns, and Ruml 2018), as well as other LM algorithms such as Dual IDA* (Zahavi et al 2008), and IBEX (Helmert et al 2019). These algorithms only store a single path and do not utilize the available memory.…”
Section: Restricted Memory Unihs Algorithmsmentioning
confidence: 99%
“…Consider the problem of estimating the probability that the plan makespan does not exceed a given deadline. Algorithms for solving such problems often apply operations like addition, multiplication and maximization, over random variables, see, e.g., (Shperberg, Shimony, and Felner 2017). In many cases the analysis found in the literature of the complexity of such algorithms focuses on the complexity stemming from the dependency graph and ignores the complexity that stems from the growth of the support, see, e.g., (Hagstrom 1988).…”
Section: Introductionmentioning
confidence: 99%